The Role of Education and Emotional Support by Maternity Nurses in Cancer Patients of Reproductive Age - Aisyah; Rustiati, Nelly (International Journal Scientific and Professional, 2025)
Women of reproductive age diagnosed with cancer often face significant emotional distress and uncertainty regarding fertility preservation and reproductive planning. Despite advancements in oncofertility care, many patients report inadequate support and limited access to reproductive education. This study explores the role of maternity nurses in providing emotional and educational support to reproductive-aged cancer patients. Using a qualitative descriptive design, in-depth interviews were conducted with maternity nurses and female cancer patients to capture their experiences and perceptions. Data were analyzed thematically and interpreted through the lens of Patient-Centered Care and Self-Efficacy theories. The findings reveal that maternity nurses play a crucial role in delivering empathetic counseling, clarifying fertility-related decisions, and fostering psychological resilience. Participants reported feeling more empowered, emotionally supported, and better informed about reproductive options due to their interactions with maternity nurses. This study concludes that integrating maternity nurses into interdisciplinary oncology teams enhances holistic care and addresses the unmet educational and emotional needs of women navigating cancer during their reproductive years. Further training and policy development are recommended to formalize their role in oncofertility services.